(untitled) (Alberta Journal of Educational Research, 2010)
This study investigates instructors’ perceptions about strengths and weaknesses of a student ratings instrument employed in their university. The sample consisted of 357 instructors in a major Canadian university where each term students are required to complete an evaluation at the end of every course. Qualitative analyses of their written responses indicate that most instructors held negative views about the ratings instrument, administration procedures, and use of results. They also reported concerns about biasing factors and the negative effect that ratings have on instructors. Few instructors provided positive comments about the validity of the ratings, the utility of ratings for the user groups, accountability, student representation, and cost efficient administration procedures. Moreover, only 25% considered ratings useful for improving teaching effectiveness.